Revisiting the cranial variability of the Dmanisi hominins - Neves, Walter; Senger, Maria Helena; Valota, Leticia; Hubbe, Mark (Anthropological Review, 2024)
The Dmanisi specimens represent the most diverse contemporaneous hominin fossils found at one single site and are key in understanding the first out -of- Africa dispersal and the origins of Homo erectus. Due to these reasons, they have]e been the focus of many studies in paleoanthropology in the last 30 years. However, there has not been any consensus on how to classify these fossils, nor has it been clarified how many species were co-living at that site. In this article, we aim to revisit the subject and contribute further to the discussion.